Estimación de riesgo de daño hepático en mujeres con preeclampsia y síndrome de HELLP en la Maternidad Ángela Loayza de Ollague (2021-2025) - Piguave Burgos, Mayerli María; Rogel Rambay, Veronica Noemi (My University, 2025)
Introduction: Preeclampsia and HELLP syndrome are severe pregnancy complications that can lead to significant liver damage. Evaluating this compromise is crucial for clinical management. Objective: The present research aimed to determine the risk of liver involvement in women with preeclampsia and HELLP syndrome, through the analysis of hepatic biomarkers and the application of the FIB-4 index, at Maternidad Ángela Loayza de Ollagüe (2021-2025), for early and effective intervention. Methodology: A retrospective, descriptive, correlational, and quantitative study was conducted, analyzing 184 medical records (2021-2025). Liver damage was assessed using serum biomarkers (ALT, AST, LDH, bilirubin, alkaline phosphatase) and the FIB-4 index. Kruskal-Wallis and chi-squared statistical tests were employed. Results: A significant association was found between the severity of preeclampsia/HELLP and biomarker levels. Patients with complete HELLP showed significantly higher ALT (median: 102 U/L; p < 0.001), AST (142 U/L; p < 0.001), LDH (736 U/L; p < 0.001), total bilirubin (1.06 mg/dL; p = 0.003), direct bilirubin (0.500 mg/dL; p = 0.008), and indirect bilirubin (0.480 mg/dL; p = 0.004). Alkaline phosphatase was not significant (p = 0.167). The FIB-4 index was useful for estimating fibrosis risk: all patients with complete HELLP showed high risk values (>2.67), indicating severe damage, while in mild/severe preeclampsia, low risk (<1.30) predominated. A significant association was observed between trimester and FIB-4 (p = 0.004). No significant association of FIB-4 with age, parity (p = 0.716), residence (p = 0.298) or comorbidities (p = 0.825). Conclusion: The FIB-4 index is validated as a non-invasive, accessible, and effective diagnostic tool for early detection and risk stratification of liver damage in pregnant women with hypertensive disorders. Its integration into standard prenatal care protocols is recommended to optimize management and improve maternal-fetal outcomes.
Introducción: La preeclampsia y el síndrome HELLP son complicaciones graves del embarazo que pueden generar daño hepático. Evaluar este compromiso es crucial para el manejo clínico. Objetivo: La presente investigación tuvo como objetivo determinar el riesgo de afectación hepática en mujeres con preeclampsia y síndrome de HELLP, mediante el análisis de biomarcadores hepáticos y la aplicación del índice FIB-4, en la Maternidad Ángela Loayza de Ollagüe (2021-2025), para una intervención temprana y efectiva. Metodología: Se realizó un estudio retrospectivo, descriptivo, correlacional y cuantitativo, analizando 184 historias clínicas (2021-2025). El daño hepático se evaluó con biomarcadores séricos (ALT, AST, LDH, bilirrubina, fosfatasa alcalina) y el FIB-4. Se emplearon pruebas estadísticas Kruskal-Wallis y chi-cuadrado. Resultados: Se halló una asociación significativa entre la severidad de preeclampsia/HELLP y los biomarcadores. Pacientes con HELLP completo mostraron elevaciones significativas de ALT (mediana: 102 U/L; p < 0.001), AST (142 U/L; p < 0.001), LDH (736 U/L; p < 0.001), bilirrubina total (1.06 mg/dL; p = 0.003), directa (0.500 mg/dL; p = 0.008) e indirecta (0.480 mg/dL; p = 0.004). La fosfatasa alcalina no fue significativa (p = 0.167). El FIB-4 fue útil para estimar el riesgo de fibrosis: todas las pacientes con HELLP completo mostraron alto riesgo (>2.67), indicando daño severo, mientras que en preeclampsia leve/severa predominó el bajo riesgo (<1.30). Se observó una asociación significativa entre el trimestre y el FIB-4 (p = 0.004). No hubo asociación significativa del FIB-4 con edad, paridad (p = 0.716), residencia (p = 0.298), o las comorbilidades (p = 0.825). Conclusión: El índice FIB-4 se valida como herramienta diagnóstica no invasiva, accesible y eficaz para la detección temprana y estratificación del riesgo de daño hepático en embarazadas con trastornos hipertensivos. Se recomienda su integración en protocolos de control prenatal para optimizar el manejo y mejorar los resultados materno-fetales.
Keywords: PREECLAMPSIA; SINDROME DE HELLP; DAÑO HEPÁTICO; DAÑO HEPÁTICO